Two Symptoms Strongly Suggest Benign Paroxysmal Positional Vertigo in a Dizzy Patient - van Dam, Victor S.; Maas, Britta D. P. J.; Schermer, Tjard R.; van Benthem, Peter-Paul G.; Bruintjes, Tjasse D. (Frontiers in Neurology, 2021)
Introduction: This prospective cohort study determined which questions in patient history are most likely to identify symptoms that are independently associated with a diagnosis of benign paroxysmal positional dizziness (BPPV) in patients presenting with dizziness, and to evaluate whether the patient’s age and type of BPPV are of influence. Methods: We included adult patients with dizziness referred to our dizziness center, Apeldoorn, the Netherlands, from December 2018 to November 2019. All patients completed a questionnaire, underwent vestibular testing and received a diagnosis. Symptoms strongly suggesting BPPV were tested with multivariable analysis to determine their independent associations with BPPV. Subgroup analysis was performed for patient age, and the type of BPPV. Results: We included a total of 885 patients, 113 of whom (13%) were diagnosed with BPPV. The duration of dizziness spells < 1 min (Q2) and dizziness provoked by rolling over in bed (Q4) were independently associated with the diagnosis BPPV. Q2 showed a sensitivity of 43%, and a specificity of 75%; Q4 scored 81% and 68%, respectively. Overall, the way patients perceived their dizziness (vertigo, light-headedness or instability) was not independently associated with the diagnosis BPPV. In younger patients, light-headedness and instability decreased the likelihood of BPPV compared to vertigo. Conclusion: The most reliable predictors for BPPV in patient history are a short duration of the dizziness spell and provocation of dizziness by rolling over in bed. Unlike younger patients, elderly patients with BPPV do not only perceive the dizziness as vertigo, but also as a feeling of instability.